2020
DOI: 10.1001/jama.2020.3182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgery vs Functional Bracing on Functional Outcome Among Patients With Closed Displaced Humeral Shaft Fractures

Abstract: IMPORTANCE Humeral shaft fractures traditionally have been treated nonsurgically, but there has been a steady increase in the rate of surgery over the past 2 decades without high-quality evidence to justify the trend.OBJECTIVE To compare the effectiveness of surgical treatment with open reduction and internal plate fixation to nonsurgical treatment with functional bracing in the treatment of closed humeral shaft fractures. DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial conducted at 2 university ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 27 publications
1
130
0
Order By: Relevance
“…The traditional anterolateral approach may cause iatrogenic injury to the radial nerve, and iatrogenic radial nerve paralysis occurs in 0–12% of cases [ 11 ]. Extensive intraoperative exposure of soft tissue in ORIF also increases the incidence of deep postoperative infection of the incision [ 12 ]. In recent years, scholars have applied MIPO technology in the treatment of humeral shaft fracture and achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional anterolateral approach may cause iatrogenic injury to the radial nerve, and iatrogenic radial nerve paralysis occurs in 0–12% of cases [ 11 ]. Extensive intraoperative exposure of soft tissue in ORIF also increases the incidence of deep postoperative infection of the incision [ 12 ]. In recent years, scholars have applied MIPO technology in the treatment of humeral shaft fracture and achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…In situations of clinical equipoise, when nonoperative and operative outcomes are similar, physicians must weigh the unique short- and long-term risks associated with surgical intervention during the pandemic. Although acute Achilles tendon rupture represents one classic example, many others exist, including management of closed displaced humeral shaft fractures [18], closed proximal humerus fractures [11], and closed displaced distal radius fractures in low-demand individuals [2]. While these pathologies have unique nuances in their management, each has high-quality evidence suggesting similar outcomes between nonoperative and operative management [2, 11, 18, 22].…”
Section: Discussionmentioning
confidence: 99%
“…To safeguard against biased interpretation of the trial data, we will interpret the results of the trial according to a blinded data interpretation scheme, 37 a procedure we have found helpful in our previous trials. [38][39][40] Briefly, an independent statistician provides the Writing Committee with blinded results from the preliminary analyses, the groups labeled as group A and group B. The Writing Committee then considers the interpretation of the results until a consensus is reached and agrees in writing on the alternative interpretations of the findings.…”
Section: Blinded Data Interpretationmentioning
confidence: 99%